Feel the Rhythm of Korea: Upaya Nation Branding Korea Selatan dalam Promosi Pariwisata di Indonesia - Annisa Jarlis; Darmansjah DJumala; Teuku Rezasyah (Fakultas Seni Rupa dan Desain ITB, 2022)
The tourism sector for South Korea is playing important roles in supporting the country's economy. The South Korean Government pays special attention to the development and promotion of its country's tourism by forming a special organization, namely the Korea Tourism Organization (KTO). This study aims to determine the process of image building and promotion of South Korean tourism through descriptive qualitative analysis using the concept of nation branding. The data collection process was carried out through interviews with the KTO and also the Indonesian public who were the audiences of the 'Feel the Rhythm of Korea' campaign. This research shows that KTO has succeeded in identifying its market so that the implementation of nation branding is carried out efficiently through digital media and brings up elements of music and dance as unique selling points in its promotion. In addition, KTO has also succeeded in attracting public interest by using a nation-brand ambassador. The conclusion of this study is that KTO's innovation in using digital media to carry out nation branding and tourism promotion is the right decision, so that it succeeds in creating a positive image and encouraging the desire of the Indonesian public to travel to South Korea.